2023
DOI: 10.1186/s12870-023-04310-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined transcriptomic and metabolomic analyses of high temperature stress response of quinoa seedlings

Abstract: Background Quinoa (Chenopodium quinoa Willd.) originates in high altitude areas, such as the Andes, and has some inherent characteristics of cold, drought, and salinity tolerance, but is sensitive to high temperature. Results To gain insight into the response mechanism of quinoa to high temperature stress, we conducted an extensive targeted metabolomic study of two cultivars, Dianli-3101 and Dianli-3051, along with a combined transcriptome analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Heat shock protein (HSP) acts as a molecular chaperone to assist protein refolding, stabilization, intracellular transport, and degradation, prevent the accumulation of damaged proteins, and maintain the stability of the intracellular environment 31 , 32 . High-temperature stress transcripome analysis of quinoa showed that HSF transcription factors such as LOC110702486 , LOC110697083 , LOC110729384 , LOC110709409 , and LOC11073445 were the core regulatory factors of transcription under high temperatures 33 . When plants are subjected to high-temperature stress, HSP accumulates a large amount of expression in a short time and participates in the stress response, but with the increase in treatment time, the stress response is weakened and HSP is degraded 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock protein (HSP) acts as a molecular chaperone to assist protein refolding, stabilization, intracellular transport, and degradation, prevent the accumulation of damaged proteins, and maintain the stability of the intracellular environment 31 , 32 . High-temperature stress transcripome analysis of quinoa showed that HSF transcription factors such as LOC110702486 , LOC110697083 , LOC110729384 , LOC110709409 , and LOC11073445 were the core regulatory factors of transcription under high temperatures 33 . When plants are subjected to high-temperature stress, HSP accumulates a large amount of expression in a short time and participates in the stress response, but with the increase in treatment time, the stress response is weakened and HSP is degraded 5 .…”
Section: Discussionmentioning
confidence: 99%
“…To safeguard cells from stress-induced damage, plants adapt by reprogramming their metabolic pathways. While there are several metabolome datasets under individual drought and heat stress (Ye et al, 2016;Sun et al, 2019;Abdelrahman et al, 2020;Lecourieux et al, 2020;Guo et al, 2021;Lu et al, 2022;Loṕez et al, 2023;Xie et al, 2023), there are only a few studies with respect to combined stress (Zinta et al, 2018;Alhaithloul et al, 2019;Lawas et al, 2019;Qaseem et al, 2019;Xie et al, 2020;Yousaf et al, 2022;Ru et al, 2023). Under combined stress, the processes of carbohydrate metabolism, amino acid metabolism and organic acid are differentially affected compared with a non-stress condition (Zinta et al, 2018;Lawas et al, 2019).…”
Section: Metabolome Responses To Combined Heat and Droughtmentioning
confidence: 99%
“…To safeguard cells from stress-induced damage, plants adapt by reprogramming their metabolic pathways. While there are several metabolome datasets under individual drought and heat stress ( Ye et al., 2016 ; Sun et al., 2019 ; Abdelrahman et al., 2020 ; Lecourieux et al., 2020 ; Guo et al., 2021 ; Lu et al., 2022 ; López et al., 2023 ; Xie et al., 2023 ), there are only a few studies with respect to combined stress ( Zinta et al., 2018 ; Alhaithloul et al., 2019 ; Lawas et al., 2019 ; Qaseem et al., 2019 ; Xie et al., 2020 ; Yousaf et al., 2022 ; Ru et al., 2023 ). Under combined stress, the processes of carbohydrate metabolism, amino acid metabolism and organic acid are differentially affected compared with a non-stress condition ( Zinta et al., 2018 ; Lawas et al., 2019 ).…”
Section: Metabolome Responses To Combined Heat and Droughtmentioning
confidence: 99%